2018
DOI: 10.1042/bsr20171657
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of haemostatic profile depending on clinicopathological determinants in breast cancer patients

Abstract: Thrombosis is one of the leading causes of mortality in cancer patients. The aim of the study was to evaluate the concentrations and activities of selected haemostatic parameters in the plasma of patients diagnosed with breast cancer (BrCa) and to make an attempt at finding associations with their levels and selected clinicopathological factors; clinical classification, histological grading, and molecular subtype of BrCa. The study involved 145 Caucasian ethnicity women. Eighty-five women aged 45–66 with prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…18,19 Concerning fibrinolytic components, several studies have shown that elevated levels of the key enzymes of the fibrinolytic system are predictors of poor patient outcome. 6,17,20,21 Our results are in line with a recent study by Rhone et al, 21 which involved 85 women with primary BC without distant metastases and a control group of 60 postmenopausal women at the same age (45-66 years), showing that BC cases had higher tPA levels than controls. Moreover, they observed a significantly higher concentration of tPA in postmenopausal BC patients as compared with premenopausal cases.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…18,19 Concerning fibrinolytic components, several studies have shown that elevated levels of the key enzymes of the fibrinolytic system are predictors of poor patient outcome. 6,17,20,21 Our results are in line with a recent study by Rhone et al, 21 which involved 85 women with primary BC without distant metastases and a control group of 60 postmenopausal women at the same age (45-66 years), showing that BC cases had higher tPA levels than controls. Moreover, they observed a significantly higher concentration of tPA in postmenopausal BC patients as compared with premenopausal cases.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, they observed a significantly higher concentration of tPA in postmenopausal BC patients as compared with premenopausal cases. 21 This mainly suggests that age and hormonal status strongly affect the biology of BC, and that tPA may lead to the development of metastasis through proteolytic degradation of the extracellular matrix.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This association was confirmed in renal cell carcinoma (150) and breast cancer; higher concentrations of PAI1 have been shown to be associated with an aggressive phenotype and a poor prognosis, with a positive correlation has been found with MMP9 (151). Rhone et al further analyzed the clinicopathological determinants of patients with invasive breast cancer and found significantly higher PAI1 concentrations in patients with ductal carcinoma compared to those with lobular carcinoma, suggesting that a high PAI1 expression predisposes to a pro-coagulant environment expressed by simultaneous activation of coagulation and fibrinolysis suppression (152). Finally, PAI1 is now considered to be a prognostic factor, particularly in breast cancer, and Li et al recently reviewed the numerous tumor promoting factors involved in the modulation of PAI1 activity (153).…”
Section: Plasma Proteinsmentioning
confidence: 99%
“…In malignancies, CRVO is considered a paraneoplastic process where dynamic interactions between the tumor cells, blood coagulation system, vascular endothelium, leucocytes and platelets contribute to the pathogenesis of CRVO. Rhone and colleagues have shown that the concentration of plasminogen activator inhibitor type 1 is increased and activity of tissue factor pathway inhibitor is reduced in patients with breast carcinoma [ 8 ]. These hematologic changes promote thrombosis.…”
Section: Discussionmentioning
confidence: 99%